The economic burden of migraine: a nationwide cost-of-illness approach from the year 2020 European Health Survey in Spain - J. Fernández-Ferro; C. Ordás-Bandera; J. Rejas-Gutiérrez; B. Ferro-Rey; S. Gómez-Lus; J.M. Láinez Andrés (Neurología (English Edition))
Background: Migraine is a chronic highly disabling disease that manifests itself with recurrent episodes of headache. The objective of the study was to ascertain the cost-of-illness (COI) of migraine from the perspective of Society in Spain and to characterize its excess cost. Methods: The nationwide year-2020 European-Health-Survey-in-Spain was used; 1442 persons with migraine (77.3% women, 52.5 years) and 4288 without migraine (76.7% women, 52.8 years) were abstracted by propensity score optimal matching. COI accounted healthcare resources utilization (HRU) and non-HRU (productivity loss). Costs were expressed as Per-Patient-Per-Year (PPPY) in Euros year 2020, and the excess cost was computed as the difference between persons with and without migraine. Results: The PPPY cost was more than double in persons with migraine; euro5862 vs euro2981; excess cost of euro2881euro (95% CI: 2410-3353, P < 0.001), mainly attributable to labour productivity loss; euro1928 (1532-2325, P < 0.001) annually (66.9% of total excess cost). This excess labour cost is explained by the greater number of additional days of absenteeism, 22.35 (16.12; 28.57), and presenteeism, 31.39 (27.36; 35.41) in persons with migraine, P < 0.001 in both cases. National Health System (NHS)-funded healthcare PPPY cost represented the 29.0% of total excess cost; euro836 (618-1055), this because higher utilization of all-type medical visits. Conclusion: In Spain, persons with migraine showed a meaningful excess cost compared with persons without migraine, particularly due to labour cost component, although the economic cost to the NHS was also considerable. Given the high prevalence of migraine, its overall attributable economic impact for Spain might range between 10 394 and 14 cost 230 million Euros in year 2020. Resumen: Introducción: La migraña es una enfermedad incapacitante que se manifiesta con episodios recurrentes de cefalea. El objetivo del estudio fue determinar el coste de la migraña desde la perspectiva de la sociedad en España, y caracterizar el exceso de coste debido a la misma. Métodos: Se utilizó la Encuesta Europea de Salud en España 2020, obteniéndose 1.442 personas con migraña (77,3% mujeres, 52,5 años) y, mediante emparejamiento óptimo con índice de propensión, 4.288 controles sin migraña (76,7% mujeres, 52,8 años). Se contabilizó utilización de recursos sanitarios y pérdidas de productividad laboral. Los costes se expresaron como coste-anual-por-persona, computándose como exceso el coste diferencial entre personas con y sin migraña. Resultados: El coste-anual-por-persona con migraña duplicó al observado en personas sin migraña; 5.862euro vs. 2.981euro, con un exceso de 2.881euro (IC95%: 2.410–3.353, p < 0,001). El exceso de coste está principalmente representado por el exceso de coste laboral: 1.928euro (1.532–2.325, p < 0,001) por persona con migraña/año (66,9% del exceso de coste total), que se explica por un numero adicional de días/año de absentismo (22,35 [16,12–28,57], p < 0,001) y presentismo (31,39 [27,36–35,41], p < 0,001) en personas con migraña comparado con controles. Un 29,0% del exceso de coste (836euro/persona con migraña/año [618−1.055], p < 0,001) está representado por costes directos por uso de recursos sanitarios financiados por el Sistema Nacional de Salud (SNS). El impacto económico atribuible a la migraña como resultado de proyectar el exceso de coste a su prevalencia en España, podría oscilar entre los 10.394 y 14.230 millones de euros en el año 2020. Conclusión: En España, las personas con migraña muestran un exceso de coste considerable, particularmente en el coste laboral, en comparación con las personas sin migraña, aunque el coste para el SNS no es desdeñable.